Are the Dioon edule (Zamiaceae) forms from San Luis Potosí proposed by Whitelock (2004) recognizable? Morphological evidence - Gabriel Rubio-Méndez; Laura Yáñez-Espinosa; Edgar G. Leija (Revista Mexicana de Biodiversidad)
Based on their morphological traits and elevation distribution, we analyzed 15 populations of Dioon edule and D. angustifolium located in the Sierra Madre Oriental in an elevation gradient from 294 to 1,314 m asl, to identify the forms proposed by Whitelock (2004). A non-parametric test was applied to find differences among elevation and populations. A discriminant analysis was applied to classify the population forms and calculate the proportion of wellclassified observations, as well as Maxent to select the environmental predictors of the population’s distribution. Ten populations were grouped into 3 forms proposed by Whitelock (2004): “angustifolium”, “edule” and “rioverde”, but 5 populations could not be classified as proposed forms, and they were named "tamasopo". The forms “tamasopo” and “rioverde” present intermediate values between the 2 species, with 63% of the individuals classified as “tamasopo” and 25% as “rioverde”. Individuals with greater height, diameter, leave length and leave number correspond to the “edule” form in the lowest elevation. The most important variables to define the distribution of the populations are vegetation, slope and annual precipitation.